2013
DOI: 10.1063/1.4795625
|View full text |Cite
|
Sign up to set email alerts
|

Sub-picowatt resolution calorimetry with a bi-material microcantilever sensor

Abstract: We have designed and fabricated bi-material microcantilevers with low conductance by minimizing the width and thickness of the cantilevers while keeping them suitable for detection with an optical deflection technique. The conductance of a cantilever is determined experimentally to be 330 6 20 nWK À1. Using this cantilever, we have measured less than 1 pW of heat flow through the cantilever. The thermal noise-limited resolution of the cantilever is expected to be %50 fW. Such cantilevers give us additional too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Microcantilever heaters, which are extremely sensitive to changes in thermal parameters [16][17][18][19][20][21], have been widely utilized for calorimetry [16], thermal nanotopography [17] and thermal conductivity measurements [18]. Due to the small area of the microcantilever that needs to be heated (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Microcantilever heaters, which are extremely sensitive to changes in thermal parameters [16][17][18][19][20][21], have been widely utilized for calorimetry [16], thermal nanotopography [17] and thermal conductivity measurements [18]. Due to the small area of the microcantilever that needs to be heated (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] The bimaterial cantilevers have shown a potential as a novel uncooled IR detector by exhibiting IR sensitivity similar to traditional methods but with lower cost and faster response time ($0.1-1 ms). 1,11,12 Published research has shown that a bimaterial cantilever can detect radiative power of 250 pW/Hz 0.5 at the wavelength of 650 nm, 6 or 1.3 nW/Hz 0.5 at the wavelength of 10 lm. 3 Focal plane array of bimaterial cantilevers has noise equivalent temperature difference (NETD) of 50-200 mK, which is comparable to the NETD of the most recent microbolometer IR detectors, 35-200 mK.…”
Section: Introductionmentioning
confidence: 99%
“…While the primary laser is stabilized at constant power and only used for realizing a signal-to-noise ratio that is sufficiently high for a reliable readout in the OBD (described above), a second laser is mixed in for modulation of the incident power. 31 The power of this secondary laser is attenuated by a neutral density (ND) filter of optical density 3.0, to scale the optical output back to the required range. By closing the loop in this way, the measured flux is no longer obtained from the cantilever curvature, but in stead from the control signal of the secondary laser.…”
Section: Description Of the Setupmentioning
confidence: 99%